Characteristics and trends of clinical studies primarily sponsored by China in WHO primary registries between 2009 and 2018: a cross-sectional survey - Yang Xu; Min Dong; Xuemei Liu (BMJ Open)
Objectives To analyse characteristics and developmental trends of clinical study registration primarily sponsored by China’s institutions during 2009–2018.Setting Registration information registered prior to 31 December 2018 was obtained from the International Clinical Trials Registry Platform (ICTRP) source registries, including Chinese Clinical Trial Registry, ClinicalTrials.gov, Australian New Zealand Clinical Trials Registry and International Standard Randomised Controlled Trial Number. Registration information on other ICTRP source registries was collected from the ICTRP.Design A cross-sectional analysis was performed. The studies sponsored by mainland China’s institutions (not including institutions in Hong Kong SAR, Macau SAR or Taiwan of China) as of 31 December 2018 were filtered. For duplicate registrations, only the records with the earliest registration date were included. Global registrations were summarised for comparison.Results A total of 32 557 China-sponsored studies and 478 261 global studies were included. The registered China-sponsored studies, increased from a cumulative number of 1333 in 2009 to 32 557 in 2018, were less likely to have industry involvement (14% vs 30%) and more likely to be registered prospectively (63% vs 45%) than the global registrations during 2009–2018. The top three most studied health conditions were lung cancer (4.2%), diabetes (3.8%) and ischaemic heart disease (3.2%). Depression and depressive disorders and chronic obstructive pulmonary disease (COPD) each represented 1.1% of registered China-sponsored studies. Phase 2 and phase 3 trials together accounted for 30%, notably lower than the global level (53%). The registered studies responding to an individual participant data (IPD) sharing plan had increased since 2016, but the proportions of studies indicating ‘yes’ were still at a low level and accounted for 5% of the registered China-sponsored studies and global registrations.Conclusions Clinical study registration activity in China has been substantial during 2009–2018. Some diseases with a high disease burden in China (depression and depressive disorders and COPD) were underrepresented by the proportion of registered studies. The accessibility of IPD merits improvement.